Halal Logistics: Halal Integrity and Legal Enforcement Challenges - Faradina Ahmad; M.Z. Hussein; Z.J. Husny; M. Yazid; Mazlan Z.; Rayner T.; Fauziah A.R; M. Zani; Nadia Adnan (International Journal of Supply Chain Management, 2018)
This is a review paper on the topic of halal logistic in relation to halal integrity and legal enforcement challenges. With the increased potential on halal logistic in the global and local market, there is a need towards maintaining and upholding the halal integrity of the business. This study shall focus on discovering the challenges on halal logistic industry and finding the means of improving the situation which causing a lot of concern. Moreover, the country must not miss out on this opportunities of maximizing the lucrative business in halal logistic to have a better economic and social upgrade as with this opportunity, there is a possibility of raising the standard of living of the local population with the creation of job employment in the halal logistic market. This study is based on the previous literature reviews and local halal forums/talks. The idea of this research study is to seek scholastic understanding of challenges of halal integrity in the logistic sector. This is an opportunity for the authors to contribute to the knowledge on halal logistic specifically on the better understanding of local halal legal enforcement issues by referring to the current reported news. Hence, emphasis on the problems faced by local authorities in enforcing the legal system to protect the halal logistic integrity.